2022
DOI: 10.1111/bjd.21598
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of reports about the impact of the COVID ‐19 pandemic on melanoma diagnosis

Abstract: Linked Article: Sangers TE et al. Br J Dermatol 2022; 187 :196–202.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 11 publications
1
10
0
Order By: Relevance
“…2 Contrasting and variable effects of COVID-19 on skin melanoma have been reported in literature, 1,3-5 however, differences between our and authors' data may be explained by the different rules of restriction adopted among worldwide countries. 1,4 Indeed, although a general reduction of face-to-face visits was reported during lockdown period, the dermato-oncological section maintained the same activity levels than previous years, ensuring both follow-up and first visits for patients, thus avoiding the reduction of screening visits (except during the first lockdown period).…”
mentioning
confidence: 98%
“…2 Contrasting and variable effects of COVID-19 on skin melanoma have been reported in literature, 1,3-5 however, differences between our and authors' data may be explained by the different rules of restriction adopted among worldwide countries. 1,4 Indeed, although a general reduction of face-to-face visits was reported during lockdown period, the dermato-oncological section maintained the same activity levels than previous years, ensuring both follow-up and first visits for patients, thus avoiding the reduction of screening visits (except during the first lockdown period).…”
mentioning
confidence: 98%
“…Our analysis of five studies analyzing changes in the proportion of melanoma diagnoses by stage during the pandemic revealed mixed findings. We observed reported increases and decreases in the proportions of melanoma stages 13 . Ricci and Abeni previously commented on conflicting results of studies describing the pandemic's impact on melanoma diagnosis, arguing that the small sample size of single‐institution studies has resulted in a heterogeneity of reported pandemic impacts to melanoma diagnosis.…”
Section: Discussionmentioning
confidence: 67%
“…We observed reported increases and decreases in the proportions of melanoma stages. 13 Ricci and Abeni previously commented on conflicting results of studies describing the pandemic's impact on melanoma diagnosis, arguing that the small sample size of single-institution studies has resulted in a heterogeneity of reported pandemic impacts to melanoma diagnosis. Our analysis of changes in proportions of melanoma staging reflects this observation and indicates that larger studies are needed to better characterize the pandemic's impact on melanoma tumor burden.…”
Section: Stagingmentioning
confidence: 99%
“…The reduction in the number of melanoma diagnoses in 2020 (as compared with 2019) was minor and likely related to the COVID-19 pandemic. However, reports concerning the impact of COVID-19 in the number of annual melanoma diagnoses have been inconsistent [ 14 ].…”
Section: Discussionmentioning
confidence: 99%